Social Responsibility of Commercial and Non-Commercial Radio in Facing the Challenges of Technology Disruption and Covid-19 Pandemic: Applications of Social Responsibility Theory - Gunawan Sapto Nugroho; Elvia Rosantina Shauki (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study is intended to find out how the influence of technological disruption and the COVID-19 pandemic on the implementation of programs and activities related to the achievement of a sustainable social activity strategy on 3 (three) types of radio, namely RRI, An-Nasihah Radio, and Gamasi Radio, and to find out how the strategy implemented by the three types of radio in the midst of the era of technological disruption and the COVID-19 pandemic. This study uses descriptive qualitative methods through semi-structured interviews which are analyzed using content, thematic, and constant comparative analysis. This research was conducted by applying the theory of Technology Disruption and the theory of Corporate Social Responsibility. The results showed that the three radios studied were affected by technological disruption and Covid-19. Each of these radios has made innovations in facing the challenges of technological disruption and COVID-19, namely making innovations in presenting broadcast programs (radio applications) via Facebook, Instagram, YouTube, websites and also applications on the Appstore and Playstore, creating a complete radio marketplace program. with prices (live), changing the work pattern of broadcasting from home, collaborating with influencers in broadcasting and presenting informative news content related to COVID-19 and utilizing social media and launching the RRI PLAY GO application. Furthermore, the results of the study showed that, of the three radios observed, Gamasi was the most active radio in carrying out its CSR activities in the form of the “Sharing Program” by making visits and entertainment to orphanages and prisons, distributing food packages for the underprivileged in around the studio and the community on the islands in the South Sulawesi region. Radio Gamasi is classified in stage 4 of CSR theory (ethical theory) considering that Radio Gamasi has carried out a program of sharing to the community.